PENGARUH LAMA FERMENTASI Trametes sp. TERHADAP KADAR BAHAN KERING, KADAR ABU, DAN KADAR SERAT KASAR DAUN NENAS VARIETAS Smooth cayene - Styawati, Nur Eka; ., Muhtarudin; ., Liman (JURNAL ILMIAH PETERNAKAN TERPADU, 2014)
The main problem in developing of ruminant production in Indonesia is the difficulty in fulfillingthe availability of feed continually, either the quality or the quantity. The abundant pineappleleaves are potensial to be feed stuff. However, the crude fiber content of pineapple leaves is high.Therefore, the pineapple leaves will be fermented by day treatment to reduce the high crude fibercontent. The aimed of the study to determine the effect of the best fermentation duration and todetermine the effect of Trametes sp. on dry metter, ash content, and crude fiber content ofpineapple leaves of Smooth cayene variety.This study was done in the Laboratory of Animal Feed, Department of Animal Husbandry, Facultyof Agriculture, University of Lampung. The treatments were arranged by using CompletelyRandomized Design (CRD) with four treatments and four replications. The treatment consisted ofstorage during 0 day, 2 days, 4 days, 6 days. The dates of observation was analyzed by usingvariance analysis with significant level of 5% and or 1%. The polynomial orthogonal was usedafter the variance analysis showed the significant result.The result of this study showed that the treatment of storage duration of 0 day, 2 days, 4 days, 6days were significantly different (P<0,01) on dry matter content, ash content, and crude fibercontent. The duration of Trametes sp. Fermentation was significantly different to the content ofdry matter, crude fiber, ash. Longer duration of fermentation, more decrease the content of drymatter, crude fiber, and ash. According to the regresion equality of dry matter Y=12,11-0,61x(R2=0,84, r=0,92), crude fiber content Y=26,08-1,81x (R2=0,69, r=0,83), and ash content Y=7,39-0,47x (R2=0,73, r=0,85).